Intermittent Screening and Treatment or Intermittent Preventive Treatment With Dihydroartemisinin-Piperaquine Versus Intermittent Preventive Treatment With Sulfadoxine-Pyrimethamine for the Control of Malaria During Pregnancy in Western Kenya: An Open-label, 3-Group, Randomized Controlled Superiority Trial. Issue 4 (December 2016) - Desai, Meghna; Gutman, Julie; L'lanziva, Anne; Otieno, Kephas; Juma, Elizabeth; Kariuki, Simon; Ouma, Peter; Were, Vincent; Laserson, Kayla; Katana, Abraham; Williamson, John; ter Kuile, Feiko O.
Abstract : ( Lancet . 2015;386:2507–2519) In sub-Saharan Africa, there are >32 million pregnancies annually. As this is a malaria-endemic region, it is estimated approximately 12 million women who have live births (45% of live births) would be exposed to malaria infection each year. The World Health Organization (WHO) recommends intermittent preventive treatment with sulfadoxine-pyrimethamine during the second and third trimester for parturients living in malaria-endemic areas. Although this strategy has been effective, concerns are being raised due to an increase in parasite resistance. The aim of this current study was to assess the efficacy and safety of 2 alternative strategies: intermittent screening with malaria rapid diagnostic tests and treatment of women who test positive with dihydroartemisinin-piperaquine, and intermittent preventive treatment with dihydroartemisinin-piperaquine.